(METAL CHILDREN OF PORT KETAPANG: THE REALITY OF POVERTY IN THE IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT) - Eka Nanda Agustin; Hary Priyanto; Safrieta Jatu Permatasari (RADJA PUBLIKA, 2025)
The presence of metal children at the Ketapang crossing pier is a picture of poverty. From an economic perspective, metal children were formed due to the pressure of the cost of living which was getting bigger and bigger, ultimately forming a common culture based on equal social feelings that were passed down from generation to generation. Metal children are vulnerable to physical, sexual violence, drug abuse, alcohol abuse, and life threats. The government must be present to handle and empower it in a sustainable manner. The aim of the research is to describe and analyze the efforts of the Ketapang Village Government in alleviating child poverty through an empowerment model. Researchers applied a qualitative descriptive approach. Based on the analysis of research findings, metal children are in a condition of chronic helplessness, metal children's activities at ports have the potential to endanger safety and lives, empowerment programs have minimal access to metal children, include appropriate resource allocation, and encourage active communities involvement. This research recommends encouraging active participation in empowerment, accelerating infrastructure development, designing specific empowerment programs, the need for regular monitoring and evaluation, and increasing cooperation.